Sandwich-like fiber diaphragm prepared through three-coaxial electrostatic spinning and preparation method and application of sandwich-like fiber diaphragm
Sandwich fiber separators are prepared through three-coaxial electrospinning technology, and nano-scale solid electrolytes and flame retardants are used to solve the problems of low thermal stability and conductivity of lithium-ion power battery separators, achieving higher performance and safety diaphragm preparation.
Patent Information
- Application Number
- CN202410991247.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-23
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-07-23
AI Technical Summary
The separators of existing lithium-ion power batteries have poor thermal stability and low ionic conductivity, resulting in insufficient battery safety performance and low energy density. The traditional preparation process has large thickness, cumbersome process and poor electrochemical performance.
Sandwich fiber diaphragm is prepared by using three-coaxial electrospinning technology. Nano-level solid electrolyte material is used as the main raw material for the core layer solution, flame retardant is introduced as the main raw material for the shell solution, and combined with the base membrane material, the material ratio is controlled to increase the membrane thermal stability, closed-cell flame retardancy, mechanical strength and ionic conductivity.
It successfully prepared a thinner, better thermal stability, better closed-cell flame retardant, and high ionic conductivity, which solved the problems of large thickness of the membrane, complex process, and poor electrochemical performance, and improved the The safety and energy density of the battery are provided.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion power battery diaphragm preparation, and more specifically, to a sandwich fiber diaphragm prepared by triaxial electrospinning, and a preparation method and application thereof. Background Art
[0002] With the continuous development of new energy technology, lithium-ion power batteries as a clean energy source have attracted more attention. The commercial application of lithium-ion power batteries has also attracted much attention, especially the safety performance of lithium-ion power batteries.
[0003] There are many factors that affect the safety of lithium batteries. As one of the four key components of lithium-ion power batteries, the main function of the diaphragm is to prevent internal short circuits and provide a free passage for lithium ions. The lithium-ion power battery diaphragms currently on the market are polyolefin diaphragms mainly composed of polyethylene and polypropylene, including single-layer PE, single-layer PP, and three-layer PP / PE / PP composite films. However, polyolefin diaphragms have poor thermal stability and are prone to shrinkage at high temperatures, leading to thermal runaway. In addition, the ionic conductivity of polyolefin diaphragms is low, which is not conducive to the development of high-rate performance lithium-ion power batteries. There is an urgent need to develop high-performance lithium-ion power battery diaphragms.
[0004] When preparing lithium-ion power battery separators traditionally, the commonly used method is to coat the mixed separator precursor liquid on the base membrane material. In this way, the base membrane thickness and the coating layer thickness will be around 20-40μm, making the separator thicker. However, the increase in separator thickness means that the volume and mass proportions of the separator in the same space increase, while the amount of battery active substances decreases, which is not conducive to improving the energy density of the battery. The electrospinning process can carry nano-scale raw materials, which provides a new idea for preparing power separators that are thinner than traditional processes. Patent CN110565269 proposes a method for preparing lithium-ion power battery separators by coaxial electrospinning, which uses polyurethane prepolymer and hexafluoropropylene for mixed spinning under electrospinning technology, but the prepared separator only improves the mechanical strength and cannot really improve the performance. Patent CN103469488A proposes a temperature difference hot melt technology to prepare lithium-ion power battery separators, and two polymers with a melting temperature difference of 30°C are prepared by electrospinning. However, the high processing temperature has a negative impact on the porosity of the separator, which is not conducive to improving the electrochemical performance of the separator. Therefore, in the field of preparation of lithium-ion power battery separators, it is still necessary to develop more effective methods to prepare high-performance separators. Summary of the invention
[0005] To solve the above problems, the first object of the present invention is to provide a method for preparing a sandwich fiber membrane by triaxial electrospinning. The preparation method creatively uses triaxial electrospinning technology to prepare a thinner membrane with excellent electrochemical performance, solving the problems of thick products, complicated processes, and poor electrochemical performance of existing coating processes.
[0006] The second object of the present invention is to provide a sandwich fiber separator prepared by the preparation method as described above.
[0007] The third object of the present invention is to provide an application of a sandwich fiber separator in the preparation of a lithium-ion power battery.
[0008] A fourth object of the present invention is to provide a lithium-ion power battery.
[0009] In order to achieve the above first object, the present invention adopts the following technical scheme:
[0010] The present invention discloses a method for preparing a sandwich fiber diaphragm by tri-coaxial electrospinning, comprising the following steps:
[0011] dissolving the base film material in a first organic solvent to obtain a middle layer solution;
[0012] Mixing the solid electrolyte with the binder glue to obtain a core layer solution;
[0013] dissolving a flame retardant in a second organic solvent to obtain a shell solution;
[0014] The fiber membrane is prepared by using a middle layer solution, a core layer solution and a shell layer solution using a three-coaxial electrospinning technology, and a sandwich fiber membrane is obtained by hot pressing and drying.
[0015] In the present invention, nano-scale solid electrolyte material is used as the main raw material of the core layer solution to improve the conductivity of the diaphragm, and flame retardant is introduced as the main raw material of the shell layer solution to improve the fire resistance of the diaphragm. Together with the middle layer solution containing the base membrane material, the proportions of the three materials are controlled under the three-coaxial electrospinning technology to obtain a sandwich-structured fiber diaphragm with better performance, which solves the problems of thick diaphragm, complicated process, poor electrochemical performance, etc. in the traditional coating process. The obtained thinner power battery diaphragm has improved thermal stability, closed-cell flame retardancy, mechanical strength and ionic conductivity while ensuring the porosity, and reduces the internal resistance of the diaphragm. It is a new type of high-performance and high-safety lithium-ion power battery diaphragm.
[0016] The traditional electrospinning process has uncontrollable jet flow, low yield, and irregular appearance of the obtained material. The three-coaxial process controls the speed by adding auxiliary airflow equipment, and the three-coaxial process can use materials with different performances at the same time to obtain membrane materials with better performance and more stable and regular morphology.
[0017] Furthermore, the solid content of the middle layer solution is 10-25%, the solid content of the core layer solution is 20-45%, and the solid content of the shell layer solution is 1-6%.
[0018] Furthermore, the substrate film material is selected from one or more of polyethylene, polyvinylidene fluoride, polypropylene, polyvinyl chloride, polystyrene, polyamide, polyethyleneimine, polyacrylonitrile, and polyimide;
[0019] The solid electrolyte is selected from oxide solid electrolytes and / or sulfide solid electrolytes;
[0020] The binder contained in the binder glue is selected from one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, carboxymethyl cellulose, polyvinyl alcohol, polyvinyl acetate, and polyvinyl butyral;
[0021] The flame retardant is selected from inorganic flame retardants and / or organic flame retardants.
[0022] Further, the oxide solid electrolyte is selected from one or more of LATP, LAGP, LLZTO, LLTO, and LLZO;
[0023] The sulfide solid electrolyte is selected from one or more of LPSBr, LPSCl, LPSI, LGePS, LSnPS, and LSiPS;
[0024] The inorganic flame retardant is selected from chlorinated paraffin and / or ammonium polyphosphate (APP);
[0025] The organic flame retardant is selected from one or more of tetrabromobisphenol A bis(2.3-dibromopropyl) ether (octabromoether), poly(2,6-dibromophenylene ether) PO-64P, FM-935, BTPAE, and triphenyl phosphate (TPP).
[0026] Further, during the triaxial electrospinning process, the voltage is 10-25 kV, and illustratively, the voltage may be 10 kV, 15 kV, 20 kV, 25 kV, etc.;
[0027] The injection speed of the middle layer solution is 0.004-0.04 mL / min. Exemplarily, the injection speed of the middle layer solution can be 0.004 mL / min, 0.006 mL / min, 0.008 mL / min, 0.01 mL / min, 0.012 mL / min, 0.014 mL / min, 0.016 mL / min, 0.018 mL / min, 0.02 mL / min, 0.022 mL / min, 0.024 mL / min, 0.026 mL / min, 0.028 mL / min, 0.03 mL / min, 0.032 mL / min, 0.03 mL / min, 0.036 mL / min, 0.038 mL / min, 0.04 mL / min, etc. The injection speed of the core layer solution is 0.002-0.03 mL / min. Exemplarily, the injection speed of the core layer solution can be 0.002 mL / min, 0.004mL / min, 0.006mL / min, 0.008mL / min, 0.01mL / min, 0.012mL / min, 0.014mL / min, 0.016mL / min, 0.018mL / min, 0.02mL / min, 0.022mL / min, 0.024mL / min, 0.026mL / min, 0.028mL / min, 0.03mL / min, etc.; the injection speed of the shell solution is 0.002-0.01mL / min. Exemplarily, the injection speed of the shell solution can be 0.002mL / min, 0.003mL / min, 0.004mL / min, 0.005mL / min, 0.006mLmin, 0.007mL / min, 0.008mL / min, 0.009mL / min, 0.01mL / min, etc. In order to ensure the stability of the membrane material framework, the injection speed of the middle layer solution should be greater than the injection speed of the core layer solution, and the injection speed of the core layer solution should be greater than the injection speed of the shell layer solution.
[0028] Furthermore, the injection speed ratio of the middle layer solution, the core layer solution and the shell layer solution is 8:4:1.
[0029] Furthermore, the hot pressing temperature is 60-90° C., the hot pressing time is 2-10 min, and the hot pressing pressure is 0.4-0.8 MPa.
[0030] Further, the first organic solvent is selected from one or more of N-methylpyrrolidone, n-butanol, xylene, and tetrachloroethylene;
[0031] The second organic solvent is selected from one or more of tetrahydrofuran, chloroform, acetone, methanol, ethanol, ether, carbon tetrachloride, acetic acid and the like.
[0032] In order to achieve the above second purpose, the present invention adopts the following technical solutions:
[0033] The invention discloses a sandwich fiber diaphragm prepared by the preparation method as described above.
[0034] In order to achieve the third object, the present invention adopts the following technical solutions:
[0035] The present invention discloses an application of the sandwich-like fiber separator described above in the preparation of a lithium-ion power battery.
[0036] In order to achieve the fourth objective, the present invention adopts the following technical solutions:
[0037] The present invention discloses a lithium ion power battery comprising the sandwich-like fiber separator described above.
[0038] The beneficial effects of the present invention are as follows:
[0039] In the present invention, the triaxial electrospinning technology is creatively used to successfully prepare a thinner, better thermally stable, better closed-cell flame retardant, high ion conductivity, and low internal resistance lithium-ion power battery separator with high performance and high safety. Specifically, nano-scale solid electrolyte materials are used as the main raw materials of the core layer solution to improve the conductivity of the separator, and flame retardants are introduced as the main raw materials of the shell layer solution to improve the fire resistance of the separator, which work together with the middle layer solution containing the base film material, and then the ratio of the three materials is precisely controlled to obtain a sandwich-like fiber separator with better performance, which solves the problems of thick separators, complicated processes, and poor electrochemical performance in traditional coating processes. DETAILED DESCRIPTION
[0040] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0041] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0042] Example 1
[0043] The present invention provides a method for preparing a sandwich fiber membrane by triaxial electrospinning, and the specific steps are as follows:
[0044] 1) Weigh 2 g of polyvinylidene fluoride powder and dissolve it in N-methylpyrrolidone to obtain a middle layer solution with a solid content of 10%;
[0045] 2) Weigh 5 g of solid electrolyte LLTO and polyvinylidene fluoride glue and mix them evenly to obtain a core layer solution with a solid content of 20%;
[0046] 3) 0.2 g of ammonium polyphosphate flame retardant was mixed with carbon tetrachloride solution to obtain a shell solution with a solid content of 2%;
[0047] 4) injecting the core layer solution obtained in step 2 into the left needle of the microinjection pump, injecting the middle layer solution obtained in step 1 into the middle needle of the microinjection pump, and injecting the shell layer solution obtained in step 3 into the right needle of the microinjection pump, the middle needle is connected to the main channel, the voltage of the adjustment device is 20kV, the injection speed of the middle needle is 0.008mL / min, the injection speed of the left needle is 0.004mL / min, and the injection speed of the right needle is 0.001mL / min, and the injection speed of the middle needle, the left needle, and the right needle are always kept unchanged for triaxial electrospinning, spinning for 150min to obtain a fiber membrane;
[0048] 5) The fiber membrane obtained by spinning was hot-pressed at 65°C and 80MPa for 5 minutes, and then dried at 105°C in a vacuum environment to obtain a sandwich-like fiber separator. The sandwich-like fiber separator had a thickness of 10.5±1 μm, a porosity of 56%, and a liquid absorption and retention rate of 153%.
[0049] Example 2
[0050] The present invention provides a method for preparing a sandwich fiber membrane by triaxial electrospinning, and the specific steps are as follows:
[0051] 1) Weigh 2 g of polyvinylidene fluoride powder and dissolve it in N-methylpyrrolidone to obtain a middle layer solution with a solid content of 10%;
[0052] 2) Weigh 5 g of solid electrolyte LLTO and polyvinylidene fluoride glue and mix them evenly to obtain a core layer solution with a solid content of 30%;
[0053] 3) 0.2 g of ammonium polyphosphate flame retardant was mixed with carbon tetrachloride solution to obtain a shell solution with a solid content of 2%;
[0054] 4) injecting the core layer solution obtained in step 2 into the left needle of the microinjection pump, injecting the middle layer solution obtained in step 1 into the middle needle of the microinjection pump, and injecting the shell layer solution obtained in step 3 into the right needle of the microinjection pump, the middle needle is connected to the main channel, the voltage of the adjustment device is 20 kV, the injection speed of the middle needle is 0.016 mL / min, the injection speed of the left needle is 0.008 mL / min, and the injection speed of the right needle is 0.002 mL / min. The injection speeds of the middle needle, the left needle, and the right needle are always kept unchanged for triaxial electrospinning, and spinning for 100 min to obtain a fiber membrane;
[0055] 5) The fiber membrane obtained by spinning was hot-pressed at 65°C and 80MPa for 5 minutes, and then dried at 105°C in a vacuum environment to obtain a sandwich-like fiber separator. The sandwich-like fiber separator had a thickness of 12.5±1 μm, a porosity of 54%, and a liquid absorption and retention rate of 150%.
[0056] Example 3
[0057] The present invention provides a method for preparing a sandwich fiber membrane by triaxial electrospinning, and the specific steps are as follows:
[0058] 1) Weigh 2 g of polyvinylidene fluoride powder and dissolve it in N-methylpyrrolidone to obtain a middle layer solution with a solid content of 10%;
[0059] 2) Weigh 5 g of solid electrolyte LLTO and polyvinylidene fluoride glue and mix them evenly to obtain a core layer solution with a solid content of 40%;
[0060] 3) 0.2 g of ammonium polyphosphate flame retardant was mixed with carbon tetrachloride solution to obtain a shell solution with a solid content of 1%;
[0061] 4) injecting the core layer solution obtained in step 2 into the left needle of the microinjection pump, injecting the middle layer solution obtained in step 1 into the middle needle of the microinjection pump, and injecting the shell layer solution obtained in step 3 into the right needle of the microinjection pump. The middle needle is connected to the main channel, and the voltage of the adjustment device is 20 kV. The injection speed of the middle needle is 0.016 mL / min, the injection speed of the left needle is 0.008 mL / min, and the injection speed of the right needle is 0.002 mL / min. The injection speeds of the middle needle, the left needle, and the right needle are always kept unchanged for three-coaxial electrospinning. Spinning for 100 min to obtain a fiber membrane;
[0062] 5) The fiber membrane obtained by spinning was hot-pressed at 65°C and 80MPa for 5 minutes, and then dried at 105°C in a vacuum environment to obtain a sandwich-like fiber separator. The sandwich-like fiber separator had a thickness of 12.5±1 μm, a porosity of 53%, and a liquid absorption and retention rate of 150%.
[0063] Comparative Example 1
[0064] In this example, a PE film currently on the market is used for subsequent performance comparison. The PE film is composed of a 9 μm base film and a 1.5 μm aluminum oxide layer coated on both sides.
[0065] Comparative Example 2
[0066] In this example, the fiber membrane is prepared using the traditional single-axis electrospinning technology. The specific steps are as follows:
[0067] 1) Weigh 2 g of polyvinylidene fluoride powder and dissolve it in N-methylpyrrolidone to obtain a middle layer solution with a solid content of 10%;
[0068] 2) Weigh 5 g of solid electrolyte LLTO and polyvinylidene fluoride glue and mix them evenly to obtain a core layer solution with a solid content of 40%;
[0069] 3) 0.2 g of ammonium polyphosphate flame retardant was mixed with carbon tetrachloride solution to obtain a shell solution with a solid content of 1%;
[0070] 4) Mix the above three solutions together and inject them into a microinjection pump;
[0071] 5) adjusting the voltage of the device to 20 kV, the injection speed of the middle needle to 0.016 mL / min, spinning for 100 min, and obtaining a fiber membrane;
[0072] 6) The fiber membrane obtained by spinning was hot-pressed at 65°C and 80MPa for 5 minutes, and then dried at 105°C in a vacuum environment to obtain a sandwich-like fiber separator. The sandwich-like fiber separator had a thickness of 7.5±1 μm, a porosity of 75%, and a liquid absorption and retention rate of 135%.
[0073] Comparative Example 3
[0074] This example is to prepare the fiber membrane under low voltage and high flow rate conditions. The specific steps are as follows:
[0075] 1) Weigh 2 g of polyvinylidene fluoride powder and dissolve it in N-methylpyrrolidone to obtain a middle layer solution with a solid content of 10%;
[0076] 2) Weigh 5 g of solid electrolyte LLTO and polyvinylidene fluoride glue and mix them evenly to obtain a core layer solution with a solid content of 40%;
[0077] 3) 0.2 g of ammonium polyphosphate flame retardant was mixed with carbon tetrachloride solution to obtain a shell solution with a solid content of 1%;
[0078] 4) injecting the core layer solution obtained in step 2 into the left needle of the microinjection pump, injecting the middle layer solution obtained in step 1 into the middle needle of the microinjection pump, and injecting the shell layer solution obtained in step 3 into the right needle of the microinjection pump. The middle needle is connected to the main channel, and the voltage of the adjustment device is 6kV. The injection speed of the middle needle is 0.08mL / min, the injection speed of the left needle is 0.04mL / min, and the injection speed of the right needle is 0.01mL / min. The injection speeds of the middle needle, the left needle, and the right needle are always kept unchanged for triaxial electrospinning. Spinning for 100min to obtain a fiber membrane;
[0079] 5) The fiber membrane obtained by spinning was hot pressed at 65°C and 80MPa for 5 minutes, and then dried at 105°C in a vacuum environment to obtain a sandwich-like fiber membrane. The sandwich-like fiber membrane has a thickness of 10 to 20 μm, is not very uniform, has a porosity of 41%, and has a liquid absorption and retention rate of 110%.
[0080] Comparative Example 4
[0081] This example adopts a method of preparing a sandwich fiber diaphragm with high voltage and constant flow rate. The specific steps are as follows:
[0082] 1) Weigh 2 g of polyvinylidene fluoride powder and dissolve it in N-methylpyrrolidone to obtain a middle layer solution with a solid content of 10%;
[0083] 2) Weigh 5 g of solid electrolyte LLTO and polyvinylidene fluoride glue and mix them evenly to obtain a core layer solution with a solid content of 30%;
[0084] 3) 0.2 g of ammonium polyphosphate flame retardant was mixed with carbon tetrachloride solution to obtain a shell solution with a solid content of 2%;
[0085] 4) injecting the core layer solution obtained in step 2 into the left needle of the microinjection pump, injecting the middle layer solution obtained in step 1 into the middle needle of the microinjection pump, and injecting the shell layer solution obtained in step 3 into the right needle of the microinjection pump, the middle needle is connected to the main channel, the voltage of the adjustment device is 30 kV, the injection speed of the middle needle is 0.016 mL / min, the injection speed of the left needle is 0.008 mL / min, and the injection speed of the right needle is 0.002 mL / min. The injection speeds of the middle needle, the left needle, and the right needle are always kept unchanged for triaxial electrospinning, and spinning for 100 min to obtain a fiber membrane;
[0086] 5) The fiber membrane obtained by spinning was hot-pressed at 65°C and 80MPa for 5 minutes, and then dried at 105°C in a vacuum environment to obtain a sandwich-like fiber membrane. The sandwich-like fiber membrane had a thickness of 7.5 to 10 μm, and the high-pressure airflow was unstable, resulting in the thickness of the ejected membrane being not very uniform, the porosity being 68%, and the liquid absorption and retention rate being 140%.
[0087] Test example
[0088] The diaphragms of Examples 1-3 and Comparative Examples 1-4 were subjected to relevant performance tests, and the performance results are shown in the following table.
[0089] The membrane impedance was tested using the EIS electrochemical method.
[0090] The cycle life is tested on a blue power test system using a single soft pack.
[0091] Thermal shrinkage performance: It is carried out in a high-temperature blast drying oven. Specifically, the diaphragm is cut into a square with a side length of 10 cm and clamped between glass plates. It is placed in a blast drying oven at a constant temperature of 180°C for 0.5h, and its shrinkage is measured.
[0092] Ionic conductivity: The ionic conductivity of the diaphragm was tested by the AC impedance method on a Zenniμm electrochemical workstation. Specifically, the diaphragm was assembled into a blocked cell of "stainless steel sheet / diaphragm / stainless steel sheet" (120μL electrolyte was added to the cell) and the ionic conductivity test was performed (frequency range 0.01Hz-1M Hz, amplitude 5mV).
[0093] Capacity retention rate: NCM523 and graphite are used as the positive and negative electrodes of the soft-pack battery, and the diaphragm is used as the separator. The positive and negative electrodes are stacked in a Z shape to assemble a soft-pack battery with a capacity of 350mAh. The cycle at 1C rate is tested, and the capacity retention rate at 500 cycles.
[0094] Fire resistance: Hold one end of the diaphragm with tweezers in a glass container and burn it with a portable igniter to time the ignition time.
[0095] Table 1
[0096]
[0097] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a sandwich fiber membrane by triaxial electrospinning, characterized in that: The steps include: dissolving the base film material in a first organic solvent to obtain a middle layer solution; Mixing the solid electrolyte with the binder glue to obtain a core layer solution; dissolving a flame retardant in a second organic solvent to obtain a shell solution; The fiber membrane is prepared by using a middle layer solution, a core layer solution and a shell layer solution using a three-coaxial electrospinning technology, and a sandwich fiber membrane is obtained by hot pressing and drying.
2. The preparation method according to claim 1, characterized in that: The solid content of the middle layer solution is 10-25%, the solid content of the core layer solution is 20-45%, and the solid content of the shell layer solution is 1-6%.
3. The preparation method according to claim 1, characterized in that: The base film material is selected from one or more of polyethylene, polyvinylidene fluoride, polypropylene, polyvinyl chloride, polystyrene, polyamide, polyethyleneimine, polyacrylonitrile and polyimide; The solid electrolyte is selected from oxide solid electrolytes and / or sulfide solid electrolytes; The binder contained in the binder glue is selected from one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polytetrafluoroethylene, carboxymethyl cellulose, polyvinyl alcohol, polyvinyl acetate, and polyvinyl butyral; The flame retardant is selected from inorganic flame retardants and / or organic flame retardants.
4. The preparation method according to claim 3, characterized in that: The oxide solid electrolyte is selected from one or more of LATP, LAGP, LLZTO, LLTO, and LLZO; The sulfide solid electrolyte is selected from one or more of LPSBr, LPSCl, LPSI, LGePS, LSnPS, and LSiPS; The inorganic flame retardant is selected from chlorinated paraffin and / or ammonium polyphosphate; The organic flame retardant is selected from one or more of tetrabromobisphenol A bis(2.3-dibromopropyl) ether (octabromoether), poly(2,6-dibromophenylene ether) PO-64P, FM-935, BTPAE, and triphenyl phosphate.
5. The preparation method according to claim 1, characterized in that: During the triaxial electrospinning process, the voltage is 10-30 kV, the injection propulsion speed of the middle layer solution is 0.004-0.04 mL / min, the injection speed of the core layer solution is 0.002-0.03 mL / min, and the injection speed of the shell layer solution is 0.002-0.01 mL / min, and the injection speed of the middle layer solution is greater than the injection speed of the core layer solution, and the injection speed of the core layer solution is greater than the injection speed of the shell layer solution; Preferably, the injection speed ratio of the middle layer solution, the core layer solution and the shell layer solution is 8:4:
1.
6. The preparation method according to claim 1, characterized in that: The temperature of the hot pressing is 60-90° C., the time of the hot pressing is 2-10 min, and the pressure of the hot pressing is 0.4-0.8 MPa.
7. The preparation method according to claim 1, characterized in that: The first organic solvent is selected from one or more of N-methylpyrrolidone, n-butanol, xylene, and tetrachloroethylene; The second organic solvent is selected from one or more of tetrahydrofuran, chloroform, acetone, methanol, ethanol, ether, carbon tetrachloride, acetic acid and the like.
8. A sandwich fiber diaphragm, characterized in that: The product is prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the sandwich fiber separator as claimed in claim 8 in the preparation of lithium-ion power batteries.
10. A lithium-ion power battery, characterized in that: It comprises the sandwich fiber separator as claimed in claim 8.
Citation Information
Patent Citations
Preparation method of reinforced electrostatic spinning nano-fiber lithium-ion battery separator
CN103469488A
Battery diaphragm, preparation method thereof and lithium ion battery
CN109473603A
Composite solid-state electrolyte membrane, preparation method thereof and solid-state lithium battery
CN115663278A
Preparation method of heat-resistant and flame-retardant bifunctional composite fiber membrane
CN115693016A
Nanofiber sandwich structure lithium battery diaphragm with warning function
CN117855752A
Cited By
Solid electrolyte membrane and preparation process thereof
CN122327464A